2020
DOI: 10.1038/s41419-020-2381-8
|View full text |Cite
|
Sign up to set email alerts
|

MOB2 suppresses GBM cell migration and invasion via regulation of FAK/Akt and cAMP/PKA signaling

Abstract: Mps one binder 2 (MOB2) regulates the NDR kinase family, however, whether and how it is implicated in cancer remain unknown. Here we show that MOB2 functions as a tumor suppressor in glioblastoma (GBM). Analysis of MOB2 expression in glioma patient specimens and bioinformatic analyses of public datasets revealed that MOB2 was downregulated at both mRNA and protein levels in GBM. Ectopic MOB2 expression suppressed, while depletion of MOB2 enhanced, the malignant phenotypes of GBM cells, such as clonogenic growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 42 publications
(54 reference statements)
0
39
0
Order By: Relevance
“…32 Similarly, high FAK expression and activity in GBM is corrected with poor overall survival. 28,33 Mechanistically, PNO1 interacted with THBS1. Here we provide evidence that PNO1 positively regulated the THBS1/FAK/Akt signaling in GBM cells, which was further confirmed by using individual inhibitors targeting FAK or Akt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Similarly, high FAK expression and activity in GBM is corrected with poor overall survival. 28,33 Mechanistically, PNO1 interacted with THBS1. Here we provide evidence that PNO1 positively regulated the THBS1/FAK/Akt signaling in GBM cells, which was further confirmed by using individual inhibitors targeting FAK or Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, the focal adhesion kinase (FAK)/Akt signaling was proved to participate in mediating the inhibition of cell migration and invasion of GBM cells. 28 However, the regulatory molecular mechanism of PNO1 on these pathways have not yet been fully determined. Intriguingly, the CO-IP experiments in this study indicated that THBS1 interacted with PNO1 in U251 cells, which has been reported to be associated with tumor development and progression in several types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these signaling pathways have been con rmed by scholars to be involved in the progression of tumors and different degrees of abnormal cell behaviors [12]. Excessive activation of phosphatidylinositol could lead to abnormal cell proliferation, abnormal endocytosis and exocytosis, abnormal cell metastasis and even tumor development [13].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, upregulation of RTKs such as signal transducer and activator of transcription 3 (STAT3) can affect multiple signaling pathways in GBM [ 89 ]. It has been found that STAT3 and focal adhesion kinase (FAK) have a role in the promotion of GBM cell invasion and migration [ 90 ].…”
Section: Hgf/met In Primary Malignant Brain Tumorsmentioning
confidence: 99%